The rising tide of HIV among young men who have sex with men in Brazil: insights from the Conectad@s studyResearch in context - Cristina M. Jalil; Emilia M. Jalil; Brenda Hoagland; Sandra W. Cardoso; Rodrigo Scarparo; Carolina Coutinho; Mayara Secco Torres Silva; Valdilea G. Veloso; Erin C. Wilson; Willi McFarland; Thiago S. Torres; Beatriz Grinsztejn (Elsevier, 2024)
Summary: Background: Young gay, bisexual, and other men who have sex with men (YMSM) in Latin America experience disproportionately high rates of HIV. While new case numbers have stabilised in other demographics, the incidence of HIV in this particular group continues to rise. We estimated the prevalence of HIV and sexually transmitted infections (STI) and identified correlates of new HIV diagnoses among YMSM in Brazil. Methods: Conectad@s was a respondent-driven sampling-based study to recruit and engage YMSM in HIV prevention and treatment services in Rio de Janeiro, Brazil (November 2021-October 2022). Eligibility criteria were age 18-24 years and self-identification as MSM (cis/trans) or non-binary person who have sex with men. Participants underwent HIV/STI testing and completed a socio-behavioural questionnaire. We described baseline characteristics by HIV status and used logistic regression models to identify correlates of new HIV diagnoses. Trial ID: DERR1-10.2196/34885. Findings: Among 409 participants, 370 (90.5%) self-identified as cisgender men, nine (2.2%) transgender men, and 30 (7.3%) non-binary. Median age was 21 years (IQR: 20-23), with 80 (19.6%) aged 18-19 years. Most self-identified as Black or Pardo (70.6%); 109 (26.7%) never tested for HIV. HIV prevalence was 9.8%; 50% (n = 20/40) were newly diagnosed with HIV. Only nine participants ever used PrEP and three were currently using it. Overall, 133 (32.5%) reported sexual violence in their lifetime and 102 (24.9%) reported a suicide attempt. Prevalence of active syphilis, chlamydia, and gonorrhoea were 14.4%, 15.9%, and 14.7%, respectively. New HIV diagnoses were positively associated with engaging in high-risk behaviour (aOR 4.88 [95% CI: 1.88-13.40]) and anxiety (aOR 2.67 [95% CI: 1.01-7.70]), and negatively associated with ever disclosing sexual orientation (aOR 0.19 [95% CI: 0.04-0.92]) and HIV knowledge (aOR 0.77 [95% CI: 0.59-1.01]). Interpretation: High prevalence of HIV coupled with a high proportion of new HIV diagnoses underscore a potentially growing HIV epidemic among YMSM in Brazil. Funding: National Institutes of Health (NIH), Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq) and Ministry of Health of Brazil.